إنتاج المعني الشعري في وطنيات أبي الحسن علي بن صالح الجزائري: ديوان مآسي!! وأين الآسي؟ أنموذجا - حني، عبداللطيف (جامعة 8 ماي 1945 قالمة, 2015)
This study derives its legitimacy in the tracking mechanisms for the production of meaning and methods of generating connotations in modern Algerian poetic speech, taken from the Court of (Maassi!! Wa Ayena Al-Assi?)The poet (Abi Al-Hassan Ben Saleh Al-grrari) model -, the richness of the texts which reflected the experience of poetry, and the study will seek to stand by the cessation of cash carefully closer tracking through which the various structures of text and its role in the production of meaning, and through silent in court, and reveal artistic and literary.
تستمد هذه الدراسة شرعيتها في تتبع آليات إنتاج المعنى وطرق توليد دلالاته في الخطاب الشعري الجزائري الحديث، متخذة من ديوان مآسي !! وأين الآسي؟ للشاعر أبي الحسن علي بن صالح القراري أنموذجا-، لثراء نصوصه التي عكست تجربته الشعرية، وستسعى الدراسة إلى الوقوف عليها وقف نقدية متأنية فاحصة تستجلي من خلالها مختلف البنى النصية ودورها في إنتاج المعنى، ونستنطق من خلالها المسكوت عنه في الديوان، وتكشف عن جماليته الفنية والأدبية.
Keywords: الشعر العربي -- بن صالح، أبي الحسن علي ت. 2006 م. -- الجزائر